The impact of SLCO1B1 rs4149056 on LDL-C target achievement after lipid lowering therapy optimization in men and women with familial hypercholesterolemia - Bosco, Giosiana; Di Giacomo Barbagallo, Francesco; Di Marco, Maurizio; Miano, Nicoletta; Scilletta, Sabrina; Spampinato, Salvatore; Vitale, Alessio; Di Bella, Federica; Montalbano, Maria; Di Mauro, Stefania; Filippello, Agnese; Scamporrino, Alessandra; et al. (Frontiers in Endocrinology, 2024)
Background and aims: FH women are less likely to receive intensive statin treatment and to obtain a 50% reduction of LDL-C from baseline compared to men with FH. SLCO1B1 rs4149056 might influence statin therapy compliance and thus LDL-C target achievement. Our aim was to evaluate the impact of SLCO1B1 rs4149056 on LDL-C target achievement after lipid lowering therapy (LLT) optimization in men and women with FH.Methods: This was a retrospective observational study involving 412 FH subjects with a probable or defined clinical diagnosis of FH who had had genetic analysis from June 2016 to September 2022.Biochemical analysis was obtained from all subjects at baseline and at the last follow-up after LLT optimization.Results: After LLT optimization the percentage of FH subjects on high-intensity statins decreased from the M/SLCO1B1-group to the W/SLCO1B1+ group and the same was found in LDL-C target distribution (for both p for trend < 0.01). The prevalence of SASE fear increased from the M/SLCO1B1-group to the W/SLCO1B1+ group and the same was observed in reported myalgia distribution (for both p for trend < 0.01). Logistic regression analysis showed that the W/SCLO1B1-, M/SCLO1B1+ and W/SCLO1B1+ groups were inversely associated with LDL-C target achievement (p for trend < 0.001) and the W/SCLO1B1+ group exhibited the strongest association.A low prevalence of FH women with SLCO1B1 rs4149056 were on high intensity statins and they rarely achieved LDL-C target. The genotype effect of SLCO1B1 rs4149056 could be more pronounced in FH women than men.